DETERMINAN KEPESERTAAN JAMINAN KESEHATAN NASIONAL (JKN) DI GARUT, INDONESIA: SEBUAH APLIKASI MULTIGROUP ANALYSIS - Irfan Rizki Gumilar; Asep Saepuloh (LPPM Universitas Bina Bangsa, 2023)
Jaminan Kesehatan Nasional (JKN) aims to provide affordable healthcare services to all Indonesian citizens. However, despite its admirable goals, the program has encountered challenges related to low participation rates in various regions, including Garut. While the JKN program aspires to achieve universal healthcare coverage, its effectiveness relies on the number of individuals enrolled in the program. The significance of this research lies in the need to comprehend the factors that influence individual participation in the JKN program, particularly in areas like Garut. To address these issues, this study will investigate the determinants of people's inclination to become JKN program participants and how these factors impact their actual behavior. The research will be carried out in Garut, Indonesia, involving both JKN participants and non-participants who will take part in a survey. The collected data will undergo analysis using Partial Least Square Structural Equation Modeling (PLS-SEM) to explore the cause-and-effect relationships among the variables under examination. Additionally, Multigroup Analysis (MGA) will be employed to assess whether these causal relationships differ between the two population subgroups